IDENTIFIKASI METODE PENERJEMAHAN DOKUMEN KONTRAK DARI BAHASA INGGRIS KE DALAM BAHASA INDONESIA - Roswani Siregar (LP2M Universitas Muslim Nusantara Al Washliyah, 2023)
This article explains the strategy in translating contract documents from English into Indonesian. The sample of this study were six corpuses of contract documents that contain technical terms in the economic field (accounting, management and finance). Translation strategies were used to solve difficulties in understanding the contents of the text of contract documents caused by cultural and linguistic) differences between the writer and the reader of the text which results in views on the concept of words and sentences intended by the writer. The methods commonly used by translators are direct translation which consists of literal, borrowing and calque, and indirect translation which includes transposition, modulation, equivalence and adaptation. Meaning field analysis is carried out to obtain the meaning of terms or vocabulary contained in the source language and target language. The results of the analysis show the complexity of understanding the procedures and translation methods used, namely borrowing, calque, literal, transposition, modulation, equivalence, adjustment, shift of unit structure and class, intrasystem and also the system of absorbing foreign terms. In terms of shifts in meaning, there are two types of shifts identified, namely (1) unit shifts and (2) category shifts. These two types of shifts often occur because syntactically English as the source language (SL) is differ from Indonesian as the target language (TL).